Solve the following system of equations by substitution. 2x = 6 3x – y = 9

Original conversation

User: Solve the following system of equations by substitution.
2x = 6
3x – y = 9

Weegy: Let 3x - y = 13 be equation 1 and
2x + y = 12 be eqaution two. [
On adding equation 1 and 2 the resultant equation is 5x = 25
therefore, x = 25/5
x = 5.
Now putting the value of x in any of the above equations(equtaion 1 or 2) we get the value of y.
3(5) - y = 13
15 - y = 13
Taking y on the right hand side and 13 on the left hand side of the equality the equation becomes
y = 2.
Therefore, x = 5 and y = 2. ] joyanansel1226|Points 26|

The coordinates of the vertex of the parabola given by the equation: y = x^2 - 2x - 2 is ( 1 , - 3 ) . y = x^2 - 2x - 2 y = ( x - 1 )^2 - 3 when x = 1 , y = -3 .

Added 10/29/2014 2:49:39 AM

This answer has been confirmed as correct and helpful.

There are no comments.